Coordinating for Academic Integrity at the Program Level (Canadian Perspectives on Academic Integrity, 2023)
Academic integrity practice and research has most often looked at action either at the individual instructor level (e.g., classroom strategies) or at the institutional level (e.g., policies). Scholars have called for attention to disciplinary patterns (Bretag et al, 2019; Rogerson et al, 2022) and for increased emphasis on the meso or middle levels of higher education institutions to influence change (Kenny & Eaton, 2022). A coordinated approach at the program level has the potential to better contextualize the values of academic integrity for students in a disciplinary or professional community, build the specific skills students need to avoid forms of academic misconduct of particular concern, and incorporate assessment approaches that translate to students' futures. A framework for assessing multiple approaches will be presented, along with potential limits and benefits of each approach. Participants will have an opportunity to situate their own examples and explore those of others. Participants can expect they will leave the session able to (1) articulate the importance of coordinating for academic integrity at the level of the program, and (2) identify a coordinating approach that they can try or advocate for in their own context.